Design, synthesis, and biological evaluation of new 6,N2-diaryl-1,3,5-triazine-2,4-diamines as anticancer agents selectively targeting triple negative breast cancer cells - Ahmad Junaid,; Lim, Felicia Phei Lin; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Royal Society of Chemistry, 2020)
New 6,N2-diaryl-1,3,5-triazine-2,4-diamines were designed using the 3D-QSAR model developed earlier. These compounds were prepared and their antiproliferative activity was evaluated against three breast cancer cell lines (MDA-MB231, SKBR-3 and MCF-7) and non-cancerous MCF-10A epithelial breast cells. The synthesized compounds demonstrated selective antiproliferative activity against triple negative MDA-MB231 breast cancer cells. The most active compound in the series inhibited MDA-MB231 breast cancer cell growth with a GI50 value of 1 nM. None of the tested compounds significantly affected the growth of the normal breast cells. The time-dependent cytotoxic effect, observed when cytotoxicity was assessed at different time intervals after the treatment, and morphological features, observed in the fluorescence microscopy and live cell imaging experiments, suggested apoptosis as the main pathway for the antiproliferative activity of these compounds against MDA-MB231 cells.